Facies Analyses Of The Coal-Bearing Formations in Sarawak: Implications On Their Paleogeographical Setting - MURTAZA, MUHAMMAD (2019)
This study unravels the depositional and paleogeographic history of the Tertiary coal-bearing formations in Sarawak. It involves the identification, evaluation, integration and interpretation of the diagnostic characteristics of the coal-bearing formations to reconstruct the depositional framework and paleogeographic evolution of the Tertiary succession of the Lundu (Kuching area), Mukah-Balingian and Bintulu areas. Detail facies analyses and the paleogeographic evaluation were conducted on newly exposed outcrops of the Tertiary coal-bearing formations in Sarawak. A total of sixty stratigraphic sections; eleven in Lundu, thirty five in Mukah-Balingian and fourteen in Bintulu area, totalling about 1300 metres thick were studied. Sedimentological, palynological and petrographic data have been compiled and integrated to evaluate the depositional framework and the paleogeographic evolution of these rock successions.